Organizational Agility: HR Practices for Facing Rapid Change in the Digital Era - Rio Mattajang (SEAN Institute, 2023)
Rapid technological developments and business dynamics in the digital era require organizations to be more responsive and adaptive to change. This research aims to explore the concept of organizational agility and identify Human Resource Management (HRM) practices that are effective in building organizational agility to face the challenges of rapid change. The research method used involves literature analysis with a qualitative descriptive approach. The research results show that in facing rapid changes in the digital era, the implementation of Human Resource Management (HRM) practices plays an important role in shaping organizational agility. Practices such as building flexible organizational structures, assignment of employees based on tasks, empowerment and autonomy, open feedback systems, skills development and continuous education, teamwork and collaboration, focus on employee well-being, careful recruitment and selection, and integration of technology support the goals creating a responsive and adaptive work environment. Nonetheless, challenges such as changing skill requirements, data security, organizational culture changes, system integration, and conflict resolution between employees and technology need to be addressed carefully. With continued commitment, organizations can overcome these challenges and build a solid foundation to become more responsive, innovative and competitive in the ever-evolving digital business era.